Application of the Computed Tomography to Control Parts Made on Additive Manufacturing Process. (2016) - Gapinski, Bartosz; Janicki, Piotr; Marciniak-Podsadna, Lidia; Jakubowicz, Michał
Abstract: The article presents possibilities of application computed tomography to study elements made with additive methods. 3D printing is currently growing very rapidly and already allows to execute ready-to-use, structurally complex elements consisting of one or more parts. Similarly, computed tomography (CT), as the youngest measurement technique and methods to control the geometrical size of the parts, allows to control through any element and evaluate both the quality of each individual components and their assembly. This technique is especially valuable for the evaluation of additive methods. What is more, the evaluation of porosity on the individual sections of the parts might be conducted. It is also possible to obtain information about the location and thickness of each of the outer wall and inaccessible by any other techniques of non-destructive quality control of construction elements filling the various parts of the printed parts.